Cultural Adaptation of Community Informant Tool for Detection of Maternal Depression in Rural Pakistan - Mohsin, Shamaila; Atif, Najia; Rabbani, Waqas; Tariq, Ahmaren; Khan, Shahzad Ali; Tariq, Mahjabeen; Sikander, Siham (Frontiers in Psychiatry, 2021)
Background: There is evidence that mental health issues like depression, epilepsy, substance misuse can be detected with reasonable accuracy in resource-poor settings. The Community Informant Detection Tool (CIDT) is one such tool used for the detection of mental health problems including depression. We adapt this community informant approach for the detection of maternal depression in Pakistan. Methods: Adaptation of Community Informant Detection Tool for Maternal Depression (CIDT-MD) involved five steps. First, a scoping review of the literature was conducted to select an appropriate tool for adaptation. Second, IDIs were conducted to explore the idioms of depression, perceived causes and effects of maternal depression among currently depressed and recovered mothers (n=11), mothers in law (n=6), and Primary Care Providers (Primary Care Physicians and Lady Health Supervisors) (n=6). Third, case vignettes and illustrations were created with input from a panel of mental health experts, incorporating the idioms of depression, cause, and effects for each symptom. Fourth, in order to assess the comprehensibility of the illustrations and level of understanding, Focus Group Discussions (n=4) were done with purposely selected community health workers (Lady Health Workers and Lay Peers n=28) trained in delivering maternal depression intervention. The final step was reflection and inputs by a panel of mental health experts on all the steps to finalize the content of the tool. Results: Context-specific cultural adaptation in the presentation of CIDT-MD was carried out successfully. The Community Health Workers (CHW) and Lay Peers (LP) were found to be the most appropriate persons to use the tool and act as informants. The adapted tool with its vignettes and illustrations was found to be easily understandable, comprehensible, culturally appropriate, and contextually relevant by the community health workers and peers. They could easily relate to and identify potentially depressed women with the tool. Lastly, the coding of the tool was found easy to follow as well. Conclusions: The Community Informant Detection Tool for Maternal Depression (CIDT-MD) is a culturally acceptable, easy to use tool for detecting maternal depression in community settings of Pakistan. The community informants found the content and approach relevant to the local needs.